Functional material for lithium-sulfur battery
By using nano-scale La1-xMxCrO3 or LaCr1-xMxO3 materials for positive electrode and separator modification in lithium sulfur batteries, the problem of polysulfide shuttle effect in lithium sulfur batteries is solved, significantly improving the electrochemical performance and cycle life of the battery, and reducing manufacturing costs.
Patent Information
- Application Number
- CN202311248510.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
Lithium sulfur batteries have a shuttle effect of soluble polysulfides during charging and discharging, resulting in poor electrode stability, low Coulomb efficiency and corrosion of metal lithium negative electrodes.
Nano-scale La1-xMxCrO3 or LaCr1-xMxO3 materials are used as catalytic and adsorption materials, and are prepared by sol-gel method and solid-phase method. They are used for the modification of the positive electrode and separator of lithium-sulfur batteries to prevent the shuttle of polysulfides and promote their conversion.
The electrochemical performance of lithium-sulfur batteries is significantly improved, including improving the utilization rate of active substances, mass specific capacity, cycle stability and cycle life, while reducing the manufacturing cost of the battery.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention relates to a catalytic and adsorbent material for a lithium-sulfur battery, belonging to the technical field of battery positive electrodes and diaphragms. Background Art
[0002] Lithium-sulfur batteries use sulfur and metallic lithium as the positive and negative active materials of the battery. They have a large theoretical specific capacity (1675mAh / g). Lithium-sulfur batteries have the advantages of light weight, large capacity, environmental friendliness, and easy availability of raw materials. Lithium-sulfur batteries are a type of secondary battery with great application prospects. Although lithium-sulfur batteries have the huge advantage of high energy density, they also have some problems that need to be solved, the most prominent of which is the shuttle effect of soluble polysulfides. The ether electrolytes currently used in lithium-sulfur batteries have a strong effect on the polysulfide ions Li2S, the intermediate products of charge and discharge. x (x=4-8) has strong solubility, which makes the charging and discharging process of lithium-sulfur batteries manifest as a complex "solid-liquid-solid" process. This process is accompanied by the dissociation and reconstruction of the positive electrode structure, which makes the electrode less stable. At the same time, when the lithium-sulfur battery is charging, the long-chain polysulfide ions produced by the positive electrode migrate to the negative electrode driven by the concentration gradient, react with metallic lithium to generate short-chain polysulfide ions, and migrate back to the positive electrode under the action of the electric field, and are further oxidized. This process is repeated over and over again, forming a "shuttle effect". The "shuttle effect" not only reduces the coulombic efficiency of the battery, but also causes corrosion of the metallic lithium negative electrode, increased viscosity of the electrolyte, and other problems, which deteriorates the battery performance.
[0003] Catalytic reaction is an effective way to solve the above problems. By accelerating the conversion of polysulfides, the capacity attenuation of lithium-sulfur batteries can be reduced and the coulombic efficiency can be increased. A variety of catalytically active substances and structures such as precious metals, metal oxides, metal sulfides, metal nitrides, non-metallic materials and heterogeneous structures are used in lithium-sulfur battery positive electrode materials. However, the above catalysts are expensive and the catalytic efficiency still needs to be improved. In addition, the use of microporous carbon paper, biomass film, porous carbon, etc. in the positive electrode and separator can block the shuttling of polysulfides. Inserting an intermediate layer between the sulfur positive electrode and the separator can significantly improve the utilization of active substances and capacity retention. However, the structurally independent intermediate layer has the disadvantage of a large volume and mass ratio. Using materials with both adsorption and catalytic functions for separator modification can effectively solve this problem. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a nanoscale La 1-x M x CrO3 (M is Li, Na, K, Mg, Ca, Sr, 0≤x≤0.3) or LaCr 1-x M xPreparation of O3 (M is Ti, V, Mn, Fe, Co, Ni, Cu, Zn, 0≤x≤0.3) materials, and application of the above materials in lithium-sulfur battery positive electrode and diaphragm modification. Compared with other catalytic materials, the preparation method of the nano-scale material for lithium-sulfur batteries of the present invention is simple, the catalytic and adsorption efficiency is high, and the electrochemical performance of lithium-sulfur batteries can be effectively improved, and it is suitable for industrial production. The nano-scale material has a relatively obvious adsorption effect on polysulfides, which can effectively prevent the shuttling of polysulfides. At the same time, the material can reduce the Gibbs free energy in the chemical reaction process and has a significant catalytic effect. The material is applied to positive electrode and diaphragm modification materials, which can significantly improve the utilization rate of active substances in lithium-sulfur batteries, and the mass specific capacity, cycle stability, and cycle life are significantly improved. It can be widely promoted in the industrialization of lithium-sulfur batteries and significantly reduce the manufacturing cost of lithium-sulfur batteries.
[0005] The present invention is achieved through the following technical solutions.
[0006] A nanoscale La 1-x M x CrO3 or LaCr 1-x M x Preparation of O3 materials, and application of the materials in lithium-sulfur battery positive electrode and diaphragm modification, the nanoscale La 1-x M x CrO3 or LaCr 1-x M x The O3 material is prepared by the sol-gel method and the solid phase method. The prepared material can be used as the positive electrode functional material of the lithium-sulfur battery, and can also be used as the modification material of the surface of the diaphragm. The modification material is mixed evenly with the conductive agent and the adhesive and then coated on one or both sides of the diaphragm.
[0007] The preparation method comprises the following steps.
[0008] 1) Weigh the chromium source, lanthanum source and compound containing doped ions according to the molar ratio, add an appropriate amount of deionized water to the above materials and stir thoroughly to dissolve them completely. Weigh ethylene glycol, citric acid and ammonium nitrate according to the molar ratio of 4:1:6.2, transfer them into the beaker containing metal ions and add an appropriate amount of deionized water to dissolve them completely. Put the beaker containing the metal ion solution into a 60°C water bath and stir thoroughly, then pour the organic mixture into it and mix evenly. After the solution is in a semi-sol state in the water bath, take it out and put it into a drying oven to dry to obtain a precursor; grind the dry gel into powder, and then keep it at a high temperature of 800°C for 2h to obtain nano-scale La 1-x M x CrO3 or LaCr 1-x M x O3 material.
[0009] 2) Nanoscale La 1-x M x CrO3 or LaCr 1-x M x O3 material, conductive agent and adhesive are added to the solvent in proportion, and a uniform membrane modification slurry is obtained by ball milling, grinding, stirring, etc. The slurry is evenly coated on one side or both sides of the membrane body and dried to obtain the modified membrane.
[0010] 3) Nano-scale La 1-x M x CrO3 or LaCr 1-x M x The O3 material is mixed with sublimated sulfur and conductive material in proportion, kept at 155°C for 6 hours and then naturally cooled. The mixture is ground evenly and then added into the solvent with the conductive agent and adhesive in proportion. A uniform slurry is obtained by ball milling, grinding, stirring and the like. The slurry is coated on a conductive current collector and dried to obtain a positive electrode sheet of a lithium-sulfur battery.
[0011] Preferably according to the present invention, the coating thickness applied to the separator is 1-30 μm, and the coating thickness applied to the positive electrode current collector is 10-500 μm; the conductive agent is one or more of conductive carbon black, carbon fiber, acetylene black, flake graphite, carbon nanotubes, graphene, polypyrrole, polyaniline, polyacetylene, and nano silver wire.
[0012] According to the preferred embodiment of the present invention, in the coating, nanoscale La 1-x M x CrO3 or LaCr 1-x M x The mass ratio of O3 material to conductive agent and binder is (3-9): (1-6): (0.2-1.5). 1-x M x CrO3 or LaCr 1-x M x The mass ratio of the O3 material / conductive agent / sulfur composite material to the conductive agent and the adhesive is (7-9): (0.5-1.5): (0.5-1.5).
[0013] According to the preferred embodiment of the present invention, the diaphragm body is any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene / polypropylene double-layer diaphragm, a polyethylene / polypropylene / polyethylene three-layer diaphragm, a polyimide diaphragm, a glass ceramic diaphragm, a polyamide diaphragm or a polyacrylonitrile. The thickness of the diaphragm body is not limited, and it is preferred that the diaphragm substrate can be effectively bonded to the coating to improve the stability of the lithium-sulfur battery and effectively reduce the polarization of the lithium-sulfur battery.
[0014] Preferably according to the present invention, the positive electrode current collector is aluminum foil, carbon-coated aluminum foil, or carbon cloth.
[0015] Preferably according to the present invention, the binder is one or more of epoxy resin, polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0016] According to the preferred embodiment of the present invention, the solvent in steps (2) and (3) is a mixture of one or more of water, methanol, ethanol, isopropanol, n-propanol, N-methylpyrrolidone, dimethyl sulfoxide, butanol, acetonitrile, tetrahydrofuran and N-methylformamide.
[0017] Preferably, according to the present invention, the positive electrode coating method described in steps (2) and (3) includes any one or more coating or spraying methods selected from the group consisting of dip coating, spin coating, blade coating, cast coating, uniaxial stretching and biaxial stretching, and the diaphragm functional material coating is performed by suction filtration, filter pressing, filtration or the same coating method as the positive electrode.
[0018] Preferably according to the present invention, in step (1), the chromium source, lanthanum source and compound containing dopant ions include but are not limited to chlorides, sulfates, nitrates and the like.
[0019] Preferably, according to the present invention, in step (1), the mixture of two or more of the chromium source, the lanthanum source and the compound containing the doping ion needs to be configured according to a molar ratio.
[0020] Preferably, in steps (2) and (3), the drying method includes forced air drying, vacuum drying, freeze drying, supercritical drying, etc.; the drying time and temperature depend on the degree of dryness of the positive electrode and diaphragm coating materials.
[0021] The present invention has the following advantages and positive effects.
[0022] 1) LaCrO3 belongs to the perovskite structure. The material has a high conductivity at room temperature. When some M ions with different valences replace the La position, the valence of the Cr position will change, thus making La 1-x M x The conductivity of CrO3 is significantly improved, and the induced lattice defects will make the material produce a significant catalytic effect on polysulfide lithium; after some M ions replace the Cr position, the generated nano-scale LaCr 1-x M x O3 materials will also improve the conductivity of the material, and will also have a significant catalytic effect on polysulfide lithium. Using the above two materials as positive electrode functional materials for lithium-sulfur batteries will significantly improve the electrochemical performance of lithium-sulfur batteries.
[0023] 2) The present invention uses nano-scale La 1-x M x CrO3 or LaCr1-x M x As a barrier layer for lithium polysulfide, O3 material has a large specific surface area and can effectively adsorb soluble polysulfides. At the same time, the above material also has a catalytic function, which can promote the conversion of lithium polysulfide, thereby more effectively inhibiting the diffusion of polysulfide to the negative electrode.
[0024] 3) Nano-scale La of the present invention 1-x M x CrO3 or LaCr 1-x M x The preparation method of O3 material adopts the combination of sol-gel method and solid phase method, with low reaction temperature, short time, simple process and low cost. The prepared nano-scale material has both adsorption function and catalytic function. The material is used as positive electrode functional material and diaphragm modification material, which is suitable for large-scale industrial production of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a comparison chart of different diaphragm cycles.
[0026] Figure 2 This is a comparison chart of the cycles of different positive electrode materials. DETAILED DESCRIPTION
[0027] The present invention is described in more detail below with reference to the accompanying drawings and some embodiments.
[0028] The raw materials in the examples are all commercially available products. Comparative Example
[0029] The multi-walled carbon tubes and sulfur powder were mixed in a ratio of 2:8, ground evenly in a mortar, and then hot-melted at 155°C, and 10% of the binder PVDF and 10% of the conductive agent SP were added. The slurry was prepared with N-methylpyrrolidone in an appropriate proportion and roller-coated on the aluminum foil to obtain the positive electrode. The button battery adopts the CR2025 specification, the electrode is coated on one side, and the diameter is 12mm; the electrolyte adopts a 1:1 electrolyte of dioxolane (DOL): ethylene glycol dimethyl ether (DME), and 0.15M anhydrous lithium nitrate and 1.0M lithium bis(trifluorosulfonyl)imide (LiTFSI) are added; the negative electrode adopts a 0.5mm thick metal lithium sheet with a diameter of 14mm; the battery separator adopts a commercial polypropylene separator (Celgard 2400), and the capacity of the button battery installed after 100 cycles at a rate of 0.1C is 420 mAh g -1 For specific data, please refer to Figure 1 . Example
[0030] 1) Weigh chromium nitrate and lanthanum nitrate in a molar ratio of 1:1 and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate in a molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), obtain nano-scale LaCrO3 material.
[0031] 2) Nano-scale LaCrO3 material, carbon nanotubes, and elemental sulfur were weighed in a mass ratio of 1:1:8, mixed evenly, and the sample was kept at 155°C for 6 hours, then cooled naturally, and the prepared composite material, conductive agent SP, and adhesive PVDF were weighed in a mass ratio of 8:1:1, and the sample was mixed evenly with N-methylpyrrolidone as a solvent, coated on the surface of aluminum foil, and vacuum dried to prepare a positive electrode sheet with a diameter of 12 mm. The negative electrode sheet, electrolyte, and separator were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 715 mAh g -1 For specific data, please refer to Figure 1 . Example
[0032] 1) Weigh chromium nitrate, lanthanum nitrate and calcium nitrate according to the molar ratio of 1:0.8:0.2, and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate according to the molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), obtain nano-La 0.8 Ca 0.2 CrO3 material.
[0033] 2) Nanoscale La 0.8 Ca 0.2 CrO3 material, carbon nanotubes, and elemental sulfur were weighed in a mass ratio of 1:1:8, and after being evenly mixed, the sample was kept at 155°C for 6 hours, and then naturally cooled. The prepared composite material, conductive agent SP, and adhesive PVDF were weighed in a mass ratio of 8:1:1, and the sample was evenly mixed with N-methylpyrrolidone as a solvent, coated on the surface of aluminum foil, and vacuum dried to prepare a positive electrode sheet with a diameter of 12 mm. The negative electrode sheet, electrolyte, and separator were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 1050 mAh g -1 For specific data, please refer to Figure 1 . Example
[0034] 1) Weigh chromium chloride, lanthanum chloride and magnesium chloride according to a molar ratio of 1:0.9:0.1, and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate according to a molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), obtain nano-scale La 0.9 Mg 0.1 CrO3 material.
[0035] 2) Nanoscale La 0.9 Mg 0.1 CrO3 material, carbon fiber, and elemental sulfur were weighed in a mass ratio of 1:1:8, and after being evenly mixed, the sample was kept at 155°C for 6 hours, and then naturally cooled. The prepared composite material, conductive agent SP, sodium carboxymethyl cellulose, and styrene-butadiene rubber were weighed in a mass ratio of 8:1:0.5:0.5, and the sample was evenly mixed with deionized water as a solvent, coated on the surface of carbon-coated aluminum foil, and vacuum dried to prepare a positive electrode sheet with a diameter of 12 mm, a polyethylene diaphragm with a diameter of 18 mm, a negative electrode sheet, and an electrolyte the same as those in comparative example 1, and the capacity of the button battery after 100 cycles at a rate of 0.1C was 1020 mAh g -1 For specific data, please refer to Figure 1 . Example
[0036] 1) Weigh lanthanum sulfate, chromium sulfate and iron sulfate according to the molar ratio of 1:0.9:0.1, and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate according to the molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), nano-scale LaCr 0.9 Fe 0.1 O3 material.
[0037] 2) Nano-scale LaCr 0.9 Fe 0.1 O3 material, super carbon black, and elemental sulfur were weighed in a mass ratio of 1:1:8, and after uniform mixing, the sample was kept at 155°C for 6 hours, and then naturally cooled. The prepared composite material, conductive agent SP, and adhesive PVDF were weighed in a mass ratio of 8:1:1, and the sample was mixed evenly with N-methylpyrrolidone as a solvent, coated on the surface of the carbon cloth, and vacuum dried to prepare a positive electrode sheet with a diameter of 12 mm. The diameter of the polyethylene / polypropylene / polyethylene separator was 18 mm. The negative electrode sheet and the electrolyte were the same as those in comparative example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 960 mAhg -1 For specific data, please refer to Figure 1 . Example
[0038] 1) Carbon nanotubes and elemental sulfur were weighed in a mass ratio of 2:8, mixed evenly, and the sample was kept at 155°C for 6 hours, then naturally cooled, and the prepared composite material, conductive agent SP and adhesive PVDF were weighed in a mass ratio of 8:1:1, mixed evenly with N-methylpyrrolidone as solvent, coated on the surface of aluminum foil, and vacuum dried to prepare a positive electrode sheet with a diameter of 12 mm.
[0039] 2) According to the steps of Example 1, the prepared nano-scale LaCrO3 material, the conductive agent SP and the binder PVDF were weighed in a mass ratio of 8:1:1, the sample was mixed evenly with N-methylpyrrolidone as solvent, coated on the surface of the polypropylene diaphragm, and vacuum dried to prepare a modified diaphragm with a diameter of 18 mm. The negative electrode sheet and the electrolyte were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 800 mAh g -1 For specific data, please refer to Figure 2 . Example
[0040] 1) Weigh chromium nitrate, lanthanum nitrate and lithium nitrate in a molar ratio of 1:0.7:0.3 and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate in a molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), obtain nano-scale La 0.7 Li 0.3 CrO3 material.
[0041] 2) Prepare the nanoscale La 0.7 Li 0.3 The CrO3 material, the conductive agent SP and the binder PVDF were weighed in a mass ratio of 8:1:1, and the samples were mixed evenly with N-methylpyrrolidone as a solvent, coated on one side of the polyethylene diaphragm, vacuum dried, and then coated on the other side of the diaphragm, and vacuum dried again to prepare a modified diaphragm with a diameter of 18 mm. The positive electrode sheet was obtained according to the steps of Example 5. The negative electrode sheet and the electrolyte were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 830 mAh g -1 For specific data, please refer to Figure 2 . Example
[0042] 1) Weigh lanthanum chloride, chromium chloride and cobalt chloride according to the molar ratio of 1:0.9:0.1, and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate according to the molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), nano-scale LaCr 0.9 Co0.1 O3 material.
[0043] 2) Prepared nano-scale LaCr 0.9 Co 0.1 O3 material, conductive agent SP, sodium carboxymethyl cellulose and styrene-butadiene rubber were weighed in a mass ratio of 8:1:0.5:0.5, and the sample was mixed evenly with deionized water as solvent, coated on one side of the polyethylene / polypropylene / polyethylene separator, and vacuum dried to prepare a modified separator with a diameter of 18 mm. The positive electrode sheet was obtained according to the steps of Example 5. The negative electrode sheet and the electrolyte were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 900 mAh g -1 For specific data, please refer to Figure 2 . Example
[0044] 1) Weigh lanthanum sulfate, chromium sulfate and nickel sulfate according to the molar ratio of 1:0.8:0.2, and dissolve the above samples in deionized water. Weigh ethylene glycol, citric acid and ammonium nitrate according to the molar ratio of 4:1:6.2, transfer them into a beaker and add an appropriate amount of deionized water to dissolve them completely. According to the steps of preparation method (1), nano-scale LaCr 0.8 Ni 0.2 O3 material.
[0045] 2) Prepared nano-scale LaCr 0.8 Ni 0.2 The O3 material, conductive agent SP and adhesive PVDF were weighed in a mass ratio of 8:1:1, and the samples were mixed evenly with N-methylpyrrolidone as solvent, coated on the surface of the polyethylene / polypropylene double-layer diaphragm, and vacuum dried to prepare a modified diaphragm with a diameter of 18 mm. The positive electrode sheet was obtained according to the steps of Example 5. The negative electrode sheet and the electrolyte were the same as those in Comparative Example 1. The capacity of the button battery after 100 cycles at a rate of 0.1C was 920 mAh g -1 For specific data, please refer to Figure 2 .
Claims
1. A functional material for lithium-sulfur batteries, characterized in that: The functional material is prepared by sol-gel method and solid phase method. The prepared material is nanometer-sized. 1-x M x CrO3 (M is Li, Na, K, Mg, Ca, Sr, ) or LaCr 1-x M x In O3 (M is Ti, V, Mn, Fe, Co, Ni, Cu, Zn) materials, 0≤x≤0.
3.
2. A functional material for lithium-sulfur batteries according to claim 1, characterized in that: In the coating, nanoscale La 1-x M x CrO3 or LaCr 1-x M x The mass ratio of O3 material to conductive agent and binder is (3-9): (1-6): (0.2-1.5). 1-x M x CrO3 or LaCr 1-x M x The mass ratio of the O3 material / conductive agent / sulfur composite material to the conductive agent and the adhesive is (7-9): (0.5-1.5): (0.5-1.5).
3. The method for preparing a functional material for a lithium-sulfur battery according to claim 1, characterized in that The method comprises the following steps: 1) Weigh the chromium source, lanthanum source and compound containing doping ions according to the molar ratio, add the above materials into an appropriate amount of deionized water and stir them thoroughly to dissolve them completely. Weigh ethylene glycol, citric acid and ammonium nitrate in a molar ratio of 4:1:6.2, transfer them into a beaker containing metal ions and add an appropriate amount of deionized water to dissolve them completely. Place the beaker containing the metal ion solution in a 60°C water bath and stir thoroughly, then pour the organic mixture into it and mix evenly. After the solution is in a semi-sol state in the water bath, take it out and place it in a drying oven to dry it to obtain a precursor; 2) Grind the dry gel into powder and keep it at 800℃ for 2h to obtain nano-scale La 1-x M x CrO3 or LaCr 1- x M x O3 materials; 3) Grinding the naturally cooled material into powder to finally prepare functional materials for lithium-sulfur batteries.